Iron-Catalyzed Intermolecular C−H Amination Assisted by an Isolated Iron-Imido Radical Intermediate - Zars, Ethan; Pick, Lisa; Swain, Abinash; Bhunia, Mrinal; Carroll, Patrick J.; Munz, Dominik; Meyer, Karsten; Mindiola, Daniel J. (Angewandte Chemie International Edition, 2023)
Here we report the use of a base metal complex [(tBupyrpyrr2)Fe(OEt2)] (1-OEt2) (tBupyrpyrr22−=3,5-tBu2-bis(pyrrolyl)pyridine) as a catalyst for intermolecular amination of Csp3−H bonds of 9,10-dihydroanthracene (2 a) using 2,4,6-trimethyl phenyl azide (3 a) as the nitrene source. The reaction is complete within one hour at 80 °C using as low as 2 mol % 1-OEt2 with control in selectivity for single C−H amination versus double C−H amination. Catalytic C−H amination reactions can be extended to other substrates such as cyclohexadiene and xanthene derivatives and can tolerate a variety of aryl azides having methyl groups in both ortho positions. Under stoichiometric conditions the imido radical species [(tBupyrpyrr2)Fe=N(2,6-Me2-4-tBu-C6H2)] (1-imido) can be isolated in 56 % yield, and spectroscopic, magnetometric, and computational studies confirmed it to be an S = 1 FeIV complex. Complex 1-imido reacts with 2 a to produce the ferrous aniline adduct [(tBupyrpyrr2)FeNH(2,6-Me2-4-tBu-C6H2)(C14H11)] (1-aniline) in 45 % yield. Lastly, it was found that complexes 1-imido and 1-aniline are both competent intermediates in catalytic intermolecular C−H amination.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Amination; C−H Activation; Imido; Insertion; Nitrene